Membrane potential governs lateral segregation of plasma membrane proteins and lipids in yeast - Großmann, Guido (The EMBO journal, 2006)
The plasma membrane potential is mainly considered as the driving force for ion and nutrient translocation. Using the yeast Saccharomyces cerevisiae as a model organism, we have discovered a novel role of the membrane potential in the organization of the plasma membrane. Within the yeast plasma membrane, two non‐overlapping sub‐compartments can be visualized. The first one, represented by a network‐like structure, is occupied by the proton ATPase, Pma1, and the second one, forming 300‐nm patches, houses a number of proton symporters (Can1, Fur4, Tat2 and HUP1) and Sur7, a component of the recently described eisosomes. Evidence is presented that sterols, the main lipid constituent of the plasma membrane, also accumulate within the patchy compartment. It is documented that this compartmentation is highly dependent on the energization of the membrane. Plasma membrane depolarization causes reversible dispersion of the H+‐symporters, not however of the Sur7 protein. Mitochondrial mutants, affected in plasma membrane energization, show a significantly lower degree of membrane protein segregation. In accordance with these observations, depolarized membranes also considerably change their physical properties (detergent sensitivity).